(3JeGQjf eMdhdI aj GdEbJUGO GdLRFj (B/s - (3GdTGQa, YJhs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2019)
(3CeGe fOQI GdeQGLY HGddZI GdYQHjI NGUI Jdc GdJj JJfGhd JeGQjf eMdhdI hab GdHQfGeL GdebQQ deGOI GdGbJUGO GdLRFj GdNGU HWdHI GdLPY GdeTJQc JNUU GdYdhe GdGbJUGOjI, GdJLGQjI, hYdhe GdJSjjQ (B. (3hVY GdeDda gPG GdcJGH deG dg ef LGfH JWHjbj fXQG dJYOO GdJbfjGJ aj gPG GdebjGS hJfhYgG, ceG GSJYGf HGdMd GdfehPLj deLehYI eYJHQI ef GdJeGQjf GdeMdhdI deSGYOI GdWGdH aj GJeGe hage eMGVQGJ GdGbJUGO GdLRFj (B.s
(3GdeQGLY U(B.285s
Keywords: (3GdEbJUGO GdLRFjs